Fungsi Manajemen Pengawasan Dalam Laporan Pertanggung Jawaban Keuangan Bantuan Hibah Biro Kesra Sumatera Utara - Harahap Adrie Fachrezi; Annio Indah Lestari Nasution (Universitas Labuhanbatu, 2023)
The purpose of this research is to study and analyze the function of effective supervisory management in the North Sumatra Bureau of Public Welfare Grant Financial Accountability Report. This study aims to evaluate the effectiveness of the existing control system, identify the factors that influence the success of supervision. By understanding effective controls and the factors that influence them, we can improve their controls and reduce the risk of fraud and other violations, as well as improve overall organizational performance.